2001
DOI: 10.1073/pnas.111150898
|View full text |Cite
|
Sign up to set email alerts
|

A role for estrogen receptor β in the regulation of growth of the ventral prostate

Abstract: In normal rats and mice, immunostaining with specific antibodies revealed that nuclei of most prostatic epithelial cells harbor estrogen receptor ␤ (ER␤). In rat ventral prostate, 530-and 549-aa isoforms of the receptor were identified. These sediment in the 4S region of low-salt sucrose gradients, indicating that prostatic ER␤ does not contain the same protein chaperones that are associated with ER␣. Estradiol (E2) binding and ER␤ immunoreactivity coincide on the gradient, with no indication of ER␣. In prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
318
5
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(343 citation statements)
references
References 36 publications
12
318
5
8
Order By: Relevance
“…The function of ER-b is not completely understood and it has been suggested that the receptor, acting through estrogens, may protect normal prostate epithelial from undergoing unscheduled cell proliferation, neoplastic transformation and from oxidative injuries. 8,13,22,[28][29][30] Even though the expression of ER-b in early prostate carcinoma and also in high grade prostatic intraepithelial neoplasia is decreased compared to normal prostatic epithelium, and some authors have found in cell line studies that its forced expression inhibits invasion and proliferation and triggers apoptosis, 31 its expression in PCa cells seems to be associated with cell survival, is highly expressed in metastatic prostate carcinoma and in our previous study was also associated with higher Gleason grades. 8,15,[32][33][34] Of note, ER-b, via an AP1-like antioxidant response element, may regulate expression of quinone reductase, an enzyme implied in control of ROS and free radicals.…”
Section: Discussionmentioning
confidence: 54%
“…The function of ER-b is not completely understood and it has been suggested that the receptor, acting through estrogens, may protect normal prostate epithelial from undergoing unscheduled cell proliferation, neoplastic transformation and from oxidative injuries. 8,13,22,[28][29][30] Even though the expression of ER-b in early prostate carcinoma and also in high grade prostatic intraepithelial neoplasia is decreased compared to normal prostatic epithelium, and some authors have found in cell line studies that its forced expression inhibits invasion and proliferation and triggers apoptosis, 31 its expression in PCa cells seems to be associated with cell survival, is highly expressed in metastatic prostate carcinoma and in our previous study was also associated with higher Gleason grades. 8,15,[32][33][34] Of note, ER-b, via an AP1-like antioxidant response element, may regulate expression of quinone reductase, an enzyme implied in control of ROS and free radicals.…”
Section: Discussionmentioning
confidence: 54%
“…Contrary to the ERa that is expressed at a higher level in stromal cells and seems to be involved in the pathogenesis of BPH, 2,11 the ERb, through activation by its putative ligand 5a-androstane-3b, 17b-diol, was reported to suppress the growth of the ventral prostate and to decrease the AR content in rodents. 21,22 Accordingly, there have been several studies describing that a loss of ERb expression is seen in high-grade prostate intraepithelial neoplasia and high-grade dysplasia compared with normal prostate epithelium expressing ERb. [23][24][25] Recent experimental studies have demonstrated that ERb behaves as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that 3βAdiol can bind to both ERα and ERβ with approximately 30-fold and 14-fold lower affinity relative to that of E2, respectively, suggesting slight specificity for ERβ [13]. 3βAdiol has been extensively characterized as an ERβ ligand in in vitro ERβ-promoter driven luciferase assays [18,19], gene expression assays [20,21], and in vivo prostate and prostate cancer models [22,23]. 3βAdiol has been shown to play a well defined role in prostate cancer etiology as an ERβ ligand.…”
Section: Discussionmentioning
confidence: 99%
“…3βAdiol has been shown to play a well defined role in prostate cancer etiology as an ERβ ligand. Weihua et al demonstrated that 3βAdiol is anti-proliferative in prostate cancer via activation of ERβ [22,23]. The cytochrome P450 CYP7B1 has been shown to be the primary enzyme responsible for the inactivation and elimination of 3βAdiol [24,25].…”
Section: Discussionmentioning
confidence: 99%